Spray, droplet evaporation, combustion, and emission characteristics of future transport fuels for compression-ignition engines: A review - Leang So Khuong; Nozomu Hashimoto; Osamu Fujita (Journal of Traffic and Transportation Engineering (English ed. Online), 2024)
This review examines the potential of hydrogen, ammonia, and biodiesel as alternative fuels, focusing on spray dynamics, droplet evaporation, combustion, and emissions. Hydrogen offers superior combustion characteristics but faces challenges in NOx emissions. Strategies like non-premixed direct injection, increased intake boost pressure, and low-pressure EGR are suggested for robust hydrogen combustion in compression-ignition engines. Control of hydrogen start of injection (SOI) and water injection (WI) are identified as effective techniques for reducing NOx emissions. Ammonia shows inferior combustion and higher NOx and unburned NH3 emissions in the same conditions as conventional fuels with conventional engines. Understanding ammonia spray and evaporation conditions is significant for optimizing an ammonia-air mixture and minimizing wall impingement and ammonia trap in the crevice, thereby improving combustion and emission reduction. Increasing intake pressure, injection pressure, and EGR rate, employing a turbulent jet, and preheating ammonia improve efficiency and reduce NOx emissions. Utilizing ammonia combustion requires the implementation of after-treatment systems such as NH3 adsorber and DeNOx catalysts to mitigate unburned NH3 and NOx emissions. Biodiesel affects the fuel supply system, combustion, and emission characteristics according to its viscosity and density. Increasing injection pressure and blending with volatile fuels enhance spray and combustion. Optimum biodiesel preheating temperatures for the injection pump and injector are crucial for achieving the best pump capacity and spray formation. By utilizing biodiesel-PODE blends and investigating low-temperature biodiesel combustions, there is potential to improve thermal efficiency and PM-NOx trade-off. Therefore, carbon-neutral fuel adoption should be accelerated to mitigate CO2 emissions, highlighting the importance of combustion techniques and emissions reduction strategies.